2020
DOI: 10.1037/pro0000310
|View full text |Cite
|
Sign up to set email alerts
|

Alternative psychotherapies: Conceptual elucidation and epidemiological framework.

Abstract: This article elucidates and defines alternative psychotherapies, as well as describing the variables that explain why some professional psychologists are prone to endorse these practices. First, the novel concept of "Complementary and Alternative Psychotherapies" (CAP) is defined within the framework of the established hierarchy of clinical evidence. Second, we report a literature review to aid understanding of the main variables explaining why some clinicians prefer CAP. We review rejection of scientific reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Myths in Psychology are defined as beliefs about human behavior that are inconsistent with the available scientific evidence but that exhibit great social support ( Lilienfeld et al, 2010 ; Stanovich, 1992 ). Contrary to certain expectations, these misconceptions are not only believed by people outside of Psychology, but also prevail among professionals within this discipline ( Fasce & Adrián-Ventura, 2020 ; Furnham & Hughes, 2014 ; Galassi & Gersh, 1993 ; Hooper, 2006 ; Houben et al, 2019 ; Lilienfeld et al, 2013 ; Torres, Boccacini & Miller, 2006 ). Although some studies show that university studies reduce the belief in myths ( Bensley, Lilienfeld & Powell, 2014 ; Hughes et al, 2015 ; Sibicky, Klein & Embrescia, 2020 ), it has also been shown that having university studies does not eliminate the belief in myths nor are these beliefs fully replaced with explanations from scientific psychology ( Hughes et al, 2015 ; Lyddy & Hughes, 2012 ; Root & Stanley, 2017 ).…”
Section: Introductionmentioning
confidence: 78%
“…Myths in Psychology are defined as beliefs about human behavior that are inconsistent with the available scientific evidence but that exhibit great social support ( Lilienfeld et al, 2010 ; Stanovich, 1992 ). Contrary to certain expectations, these misconceptions are not only believed by people outside of Psychology, but also prevail among professionals within this discipline ( Fasce & Adrián-Ventura, 2020 ; Furnham & Hughes, 2014 ; Galassi & Gersh, 1993 ; Hooper, 2006 ; Houben et al, 2019 ; Lilienfeld et al, 2013 ; Torres, Boccacini & Miller, 2006 ). Although some studies show that university studies reduce the belief in myths ( Bensley, Lilienfeld & Powell, 2014 ; Hughes et al, 2015 ; Sibicky, Klein & Embrescia, 2020 ), it has also been shown that having university studies does not eliminate the belief in myths nor are these beliefs fully replaced with explanations from scientific psychology ( Hughes et al, 2015 ; Lyddy & Hughes, 2012 ; Root & Stanley, 2017 ).…”
Section: Introductionmentioning
confidence: 78%
“…The psychotherapy of drug abuse mainly focuses on mind-body therapies, such as meditation, and various other types of behavioral therapy that have been proven to be effective interventions (42). However, psychotherapy is associated with not only CAM but also psychotherapies, especially complementary and alternative psychotherapies (CAPs), and MeSH terms related to some psychotherapies, such as "biofeedback, psychology, " or "imagery, psychotherapy, " may produce similar results (43). The word "psychotherapy" may change its definition in recent years.…”
Section: Research Fields and Frontiersmentioning
confidence: 99%